Analisis Akad Mudharabah Pada Produk Perbankan - Syahrir, Sri Auliya (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Mudharabah is one of the important contracts in Islamic banking financing products based on the principle of profit sharing. This research aims to analyze the application of Mudharabah contracts in various Islamic financing products such as mudharabah accounts, working capital financing, and investment. The research method used is a literature study of literature related to Mudharabah contracts and related regulations such as Fatwa DSN. The results showed that the analysis of Mudharabah contract rules is important to understand the working mechanism of related Islamic banking products. The main difference of Mudharabah contract from conventional contracts is that it is based on the principle of profit sharing and not interest.